MANAJEMEN PESERTA DIDIK: PERSPEKTIF TEORITIS DAN PRAKTIS DALAM SISTEM PENDIDIKAN INDONESIA - Shelty D. M. Sumual; Joulanda A. M. Rawis; Diana Lililyans Sigarlaki; Toar Deliezer Bram Mambu; Hilda Anelin Tasiringan; Stevi B. Sengkey (Jurnal Manajemen Pendidikan, 2025)
Student Management (Manajemen Peserta Didik/MPD) serves as a strategic component within the education system, functioning not only to maintain administrative order but also to facilitate the holistic development of learners. This study employs a qualitative literature review approach to explore the conceptual foundations of MPD, its theoretical basis, regulatory framework, and its practical implementation in educational settings. The analysis reveals that MPD is not limited to documentation or attendance monitoring; it is intricately connected to learner development theories, character formation, mental health considerations, and the overall effectiveness of instructional processes. An ideal MPD framework must be regulation-based, responsive to individual learner needs, data-driven, and capable of fostering a psychologically safe and productive learning environment. The findings highlight the critical role of MPD in supporting the implementation of the Merdeka Curriculum and the ongoing digital transformation in education. Accordingly, MPD must be strengthened through refined service structures, collaborative leadership, and improved digital literacy. This review concludes that MPD should not be perceived as a mere administrative function but as a strategic managerial system that underpins the comprehensive quality of education.